Pengaruh Total Asset Turnover dan Net Profit Margin Terhadap Perubahan Laba Bersih pada PT. Indo Kordsa, Tbk - Tusholinah, Rizka; Puji Muniarty; Hanifah Muthiah (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
The IDX-listed manufacturing business PT. Indo Kordsa, Tbk was the site of this research. Finding out how PT. Indo Kordsa Tbk's Net Profit Margin and Total Asset Turnover affected Net Profit Changes was the driving force behind this research. This research employs an associative data format that encompasses all financial reports of PT. Indo Kordsa Tbk. The company has been listed on the IDX for 33 years, from 1990 to 2023. The data utilized for this analysis comes from PT. Indo Kordsa, Tbk's financial reports covering the years 2014–2023. Purposive sampling was utilized to determine the sample in this investigation. This research employs the following data analysis technique: (1). Among the standard assumption tests are those for autocorrelation, heteroscedasticity, multicollinearity, and normalcy (2). T- and F-tests for hypothesis testing, multiple linear regression, correlation coefficients, and determination. According to the study's findings, Total Asset Turnover (TATO) and Net Profit Margin (NPM) both have a substantial impact on Changes in Net Profit at the same time, but neither of these variables has a partial effect on Changes in Net Profit.